An expert consensus report on the clinical use of the Vycross® hyaluronic acid VYC‐25 L filler. (30th August 2021) - Segurado, María A.; Urdiales‐Gálvez, Fernando; Benítez, Paula A.; Carrasco, Sara; Díaz, Iratxe; Escoda, Nuria; Farollch‐Prats, Lisandro; Figueiredo, Vitor; Ortíz, Francisco; Sebastián, María Consuelo; Uva, Luís
Abstract: Background: The portfolio of hyaluronic acid (HA) fillers and the techniques of administration have evolved in recent years. The latest innovation in the Vycross ® range was the introduction of VYC‐25L (Juvéderm Volux ® ; Allergan plc), a first‐in‐class filler effective for chin and facial lower third remodeling. The aim here was to provide clinicians who are starting to use VYC‐25L with key advice, and to standardize procedures so that optimal and predictable outcomes can be obtained. Methods: A multidisciplinary group of experts in esthetic medicine from Spain and Portugal reviewed the properties, treatment paradigms, administration techniques, and potential complications of VYC‐25L, on the basis of which they drafted consensus recommendations for its clinical use. Results: The consensus panel provided specific recommendations focusing on the patient profile, dose, administration techniques, and the complications of VYC‐25L and their management. The panel identified five different profiles of patients who may benefit from VYC‐25L, and they drafted recommendations aimed to facilitate the treatment of these patients, namely, microgenia (women/men), masculinization (men), rejuvenation (women/men), facial laxity (women/men), and submental convexity (women/men). In terms of their safety, no specific recommendations were made beyond those established for other HA fillers. Conclusions: The evolution of esthetic medicine makes it necessary to update the clinical recommendations that guide patient assessment and treatment with the new HA fillers developed. The current consensus document addresses relevant issues related to the use of VYC‐25L on different types of patient, in an attempt to standardize procedures and help specialists obtain predictable results.